China's Integration with the World : Development as a Process of Learning and Industrial Upgrading - Lin, Justin Yifu; Wang, Yan (Washington, DC: World Bank, 2012)
The process of development is full of uncertainties, especially if it is a process of transition from a planned economy to a market oriented one. Because of uncertainties and country specificity, development must be a process of learning, selective adaptation, and industrial upgrading. This paper attempts to distill lessons from China's reform and opening up process, and investigate the underlying reasons behind China's success in trade expansion and economic growth. From its beginnings with home-grown and second-best institutions, China has embarked on a long journey of reform, experimentation, and learning by doing. It is moving from a comparative advantage-defying strategy to a comparative advantage-following strategy. The country is catching up quickly through augmenting its factor endowments and upgrading industries; but this has been only partially successful. Although China is facing several difficult challenges - including rising inequality, an industrial structure that is overly capital and energy intensive, and related environmental degradation - it is better positioned to tackle them now than it was 30 years ago. This paper reviews the drivers behind China's learning and trade integration and provides both positive and negative lessons for developing countries with diverse natural endowments, especially those in Sub-Saharan Africa.